Efektivitas Distribusi Penyaluran Pupuk Bersubsidi di Kabupaten Musi Rawas (Studi Kasus Tiga Kecamatan Sentra Beras) - Vera Octalia; Ira Primalasari (Yayasan Literasi Sains Indonesia, 2025)
The agricultural sector has received high priority from the government, one of which is the fertilizer subsidy policy. The distribution of subsidized fertilizer, applying the 5 right principles (right price, right quantity, right type, right time, right place), is crucial to implement. The purpose of this study is to determine the effectiveness of the distribution of subsidized fertilizer in Musi Rawas Regency (Case Study of Three Rice Center Districts). The respondent in this study included 2 distributors, 4 retailers, and 75 farmers. This type of research employs both qualitative and quantitative approaches and can be classified as empirical research, utilizing primary and secondary data sources. The data analysis used is descriptive analysis involving indicators of the 5 right principles. The results show that the distribution of subsidized fertilizer in Musi Rawas Regency falls into the criteria of being quite effective, with an effectiveness percentage of 77%. It can be said that there are still indicators that have not been implemented by applicable regulations. Two principal indicators fall into the Less Effective criteria, namely the right quantity indicator and the right price indicator, while the other three indicators fall into the criteria of being very effective.